Importance of Life Insurance in Meeting out Financial Needs and Security - Pandey, Dr. Tarkeshwar (International Journal of Scientific Research and Management (IJSRM), 2017)
The journey of human life, from womb to tomb is full of woes, worries and needs. Man is endowed with highly intellectual ability and he makes persistent efforts for the betterment and advancement of his. life, which gives him the highest happiness and comfort, also benefiting in that process all those who depend on him for economic security